Research on Power Demand Response of A Certain Area Power Grid for New Energy Consumption. Issue 1 (April 2021) - Zhang, Yi; Wu, Yifeng; Zhang, Feng; Cai, Jianqiang; Li, Yang; Tang, Lv
Abstract: With the rapid growth of new energy installation scale, new energy consumption is facing more and more pressure and challenge. Based on the characteristics of a certain provincial power grid, this paper starts from the point of view of promoting clean energy consumption, guiding electric heating load and other adjustable loads to optimize electricity consumption, relieving peak-shaving pressure of power grid, and strengthening the emergency regulation ability of the certain power grid, the power demand response of provincial power grid is designed and realized. This mode and methods have universal application value for provincial power grid with high proportion of new energy installation.